Mengukur Kesiapan Orang Tua Siswa Terhadap Pembelajaran Online Menggunakan Chapnick ELR - Nandang Suwela; Ismailah Ismailah; Heri Satria Setiawan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
Since the determination of the Corona Virus or Covid-19 outbreak as a pandemic by the government, there have been some major changes in living daily life in Indonesia. Almost all activities are carried out online, including teaching and learning activities which are referred to as Distance Learning (PJJ). The PJJ model is a new way of learning in Indonesia, this certainly has an impact, both on students and on parents. This research is a descriptive study that describes the opinions of the parents of students of Al-Azhar 2 Islamic Elementary School, Pasar Minggu with 20 % random sampling technique or 106 parents of all students' parents totaling + 540 people. This study used a closed survey model and data analysis with descriptive analysis. From this study, it was found that the average parents of student of Al-Azhar 2 Islamic Elementary School, Pasar Minggu answered to be doubtful or neutral about aspects of Psychological Readiness, Sociological Readiness and Financial Readiness, while for aspect of Environmental Readiness, Human Resources Readiness, Technological Readiness, Content Their Readiness state that they were ready and for Equipment Readiness they stated that they were very ready.